Subjective Outcome Evaluation of the Project P.A.T.H.S. in Different Cohorts of Students - Daniel T. L. Shek; Cecilia M. S. Ma (The Scientific World Journal)
The project P.A.T.H.S. is an indigenously developed positive youth development program in Hong Kong. In the extension phase (2009/2010 school year), subjective outcome evaluation data were collected from 231 schools involving 89,068 participants after completion of the curricula-based Tier 1 Program. With schools as the units of analysis, results showed that participants generally had positive perceptions of the program content and implementers, with over four-fifth of the participants regarded the program as helpful to them. There were some significant grade differences in the subjective outcome evaluation findings, although the related effect size was not strong. Multiple regression analyses revealed that program content and program implementers predicted perceived effectiveness of the program. The present study suggests that irrespective of cohorts, students in the junior secondary years perceived the program to be beneficial to them.